P176 Clinical pharmacology of the HIV integrase strand transfer inhibitor bictegravir. (8th June 2017) - Zhang, Heather; Custodio, Joseph; Wei, Xuelian; Wang, Hui; Wu, Amanda; Ling, John; Martin, Hal; Quirk, Erin; Elliott, Cindy; Kearney, Brian
Abstract : Introduction: Bictegravir(BIC), an investigational, once-daily, HIV integrase strand transfer inhibitor(INSTI) with potent in vitro activity against most INSTI-resistant variants, is currently in development as a single tablet regimen(STR) coformulated with FTC/TAF. Methods: BIC exposure was dose proportional following SD of 25–100mg. Steady-state accumulation was approximately 1.6x, consistent with the observed half-life of approximately 18 hours. Balanced glucuronidation and oxidation contributed to the major clearance pathways. The DDI study showed increased BIC AUC(61-74%) by CYP3A4 inhibitors voriconazole and DRV/COBI but showed a greater increase( 4x) by potent dual inhibitors of UGT1A1 and CYP3A4, ATV and ATV+COBI. Coadministration with a potent CYP3A4/UGT1A1/P–gp inducer, rifampin resulted in a 75% decrease of BIC AUC a lesser reduction(38%) was associated with the moderate CYP3A4/P–gp inducer, rifabutin. BIC was well tolerated at all doses studied. Results: The favourable BIC PK profile supports once daily dosing. DDI results are consistent with its ADME profile in which both CYP3A4 and UGT1A1contributed to BIC elimination. BIC was safe and well tolerated in healthy volunteers. Discussion: The favourable BIC PK profile supports once daily dosing. DDI results are consistent with its ADME profile in which both CYP3A4 and UGT1A1contributed to BIC elimination. BIC was safe and well tolerated in healthy volunteers.